Flaxseed lignan: Metabolism, extraction and isolation techniques, potential health benefits and food applications - Thomas, Elizabeth; Panjagari, Narender Raju; Sangita Ganguly; Suman Kapila; Ashish Kumar Singh (Indian Journal of Dairy Science, 2024)
Flaxseed lignan has been recognized as a potent phytoestrogen for the treatment of health problems such as cancer, diabetes, hyperlipidaemia, cardiovascular diseases, postmenopausal related diseases and so on. Existing literature suggests that higher dietary or supplementary intakes of lignans and other phytoestrogens have been linked to improved cognitive performance in middle-aged and older people. The lignan secoisolariciresinol diglucoside is found in abundance in flaxseed. Flaxseed lignan metabolites may offer health benefits due to their weak estrogenic or anti-estrogenic effects, antioxidant activity or other yet-to-be-identified mechanisms. The current review explores the metabolism of flaxseed lignan by gut microbiota, its bio accessibility, health benefits of flaxseed lignan in humans and the possible mechanisms, with data from animal and clinical studies in the last few years to back up that assertion, application in food and dairy industry and makes recommendations for future research.